ANALISIS PENYEBAB TINGGINYA KELUHAN PASIEN TERKAIT AKUN MOBILE JKN YANG SERING TER-LOGOUT DI RSI MUHAMMADIYAH SUMBERREJO TAHUN 2026 - Puan Maharani Hardiyanti; Enny Mar’atus Sholihah; Hermin Puji Astutik (Rena Cipta Mandiri, 2026)
Mobile JKN is a digital application developed by BPJS Kesehatan to facilitate National Health Insurance members in accessing healthcare services. However, frequent complaints about automatic account logouts remain a problem at RSI Muhammadiyah Sumberrejo, disrupting service delivery. This study aimed to identify the causes of frequent Mobile JKN account logouts. A qualitative descriptive method was employed through in-depth interviews with three purposively selected informants, supported by observation and documentation. Data were analyzed using the Miles and Huberman model. The findings showed that the main causes of account logouts were system updates, system maintenance, and account access from different devices. Other barriers included forgotten passwords and not carrying mobile phones. These problems increased service waiting time and staff workload. Providing simple educational media is recommended to improve patients' understanding and independence in using the Mobile JKN application, thereby enhancing the efficiency and quality of healthcare services.